Legal Review of Consumer Protection for Illegal Cosmetic Products in Electronic Trade According to Law Number 8 of 1999 Concerning Consumer Protection (International Forum of Researchers and Lecturers, 2025)
This study discusses consumer protection in the circulation of illegal cosmetic products through electronic commerce systems, focusing on the implementation of Law Number 8 of 1999 concerning Consumer Protection. The main problems of the research include legal regulations related to illegal cosmetics, legal provisions regarding electronic commerce, and consumer protection mechanisms against the circulation of illegal cosmetics on e-commerce platforms. This study uses a qualitative method with a normative legal research approach through literature studies, which involves primary, secondary, and tertiary data sources. The results of the study show that cosmetic distribution permits are regulated in the Regulation of the Food and Drug Supervisory Agency Number 12 of 2023 concerning the Supervision of the Manufacture and Circulation of Cosmetics. In electronic commerce, transactions occur electronically between sellers and buyers by involving a third party as the platform provider. Dispute resolution between consumers and business actors is regulated in the Consumer Protection Law through two channels, namely litigation and out-of-court dispute resolution. The research concluded that every cosmetic in circulation must have a distribution permit in the form of a BPOM Notification, and business actors are responsible for providing compensation in the form of refunds or product replacements. The research recommendations emphasize the importance of consumer prudence, honesty of business actors, and the government's firmness in handling consumer problems.